Prevalence and Pathophysiology of Anemia in Pakistani Patients with Chronic Liver Disease (CLD). A Clinical and Infectious Etiology-Based Study - Rabia Parveen, Misbah Majeed, Khadija Aftab, M. Shakil Zari Khawri Siddiqui, Anam Arshad, Farooq Ahmad Malik, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Anemia is a common but underappreciated complication of chronic liver disease (CLD), contributing to fatigue, impaired immunity, and worse clinical outcomes. In Pakistan, where viral hepatitis and alcohol‐related liver injury are prevalent, data on anemia prevalence and underlying mechanisms in CLD are scarce. Methods: We conducted a cross‐sectional study of 90 adult CLD patients recruited consecutively from Pakistan Employees Military Hospital, Rawalpindi, and The University of Lahore Teaching Hospital between January 2022 and April 2023. Demographic and clinical data were recorded, and detailed laboratory tests complete blood count, iron profile, vitamin B12 and folate levels, liver function tests, coagulation profile, and viral serologies were performed. Anemia was classified by red cell indices into microcytic, normocytic, or macrocytic subtypes and graded as mild, moderate, or severe according to WHO criteria. Etiologies of CLD were determined clinically and via imaging, with special focus on hepatitis B, hepatitis C, alcohol‐related liver disease, non‐alcoholic fatty liver disease (NAFLD), and autoimmune hepatitis. Results: The cohort’s mean age was 52 ± 12 years; 66.7% were male. Hepatitis C (44.4%) and hepatitis B (20.0%) were the most common CLD etiologies. Anemia was present in 100% of patients: microcytic in 45.6%, normocytic in 38.9%, and macrocytic in 15.6%. Moderate anemia predominated (52.2%), followed by mild (26.7%) and severe (21.1%). Microcytic anemia correlated strongly with hepatitis C and NAFLD, while macrocytic anemia was most frequent in alcoholic liver disease (p < 0.05). Conclusions: Anemia affects all CLD patients in this Pakistani cohort, with distinct morphological patterns linked to specific liver disease etiologies. Routine hematologic screening and targeted management iron supplementation, vitamin repletion, and antiviral therapy are essential to improve patient outcomes. Keywords: Anemia; Chronic liver disease; Cirrhosis; Pathophysiology; Pakistan; Hepatitis C